Pengaruh Situasi Audit, Etika, Pengalaman Dan Keahlian Terhadap Skeptisisme Pofesional Auditor (Studi Empiris Pada Kantor Akuntan Publik Se-Sumatera) - Giovanny Vermico Aritof; Rita Anugerah; Muhammad Rasuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is aims to get empirical prove about influence of audit situation, ethics, experience and expetise toward auditor professional skepticism in public accounting office (KAP) in Sumatera. Population of this research is all off auditor who work at public accounting office (KAP) in Sumatera who list at Direktori Institut Akuntan Publik Indonesia (IAPI) 2014 on all province in Sumatera island. The entire polpulation was made a reserarch sample. The data obtained through the dissemination of a questionaire and based on predeterminated criteria there are 70 quesionaire that can be proceed. The data obtained were analyzed by multiple regression by using Statistical Product Services Solution (SPSS) version 17. The result of this research indicated that audit situation , ethics, experience and expertise effect on auditor professional skepticism at public accounting office (KAP) in all province on Sumatera island. The magnitude of adjusted R squareis 69,70 give the sense that the 69,70% auditor proffesional skepticism influence by audit situation , ethics, experience and expertise, whereas 30,30% influence by other variable.Keywords : Auditor Professional Skepticism, Audit Situation , Ethics, Experience and Expertise